THE KERCH TRAFFIC INTERCHANGE: A GEOPOLITICAL DIMENSION - PERGA, Tatyana (CENTRAL ASIA AND THE CAUCASUS, 2015)
After unifying with Crimea in 2014, Russia became determined to build a traffic interchange across the Kerch Strait. A bridge across the strait has appeared and disappeared from the agenda several times. Today Moscow means business: the peninsula needs foodstuffs, energy, and water. Before the war between Russia and Ukraine, this large-scale project with its huge integration potential could have claimed a geopolitical status. Today, when international isolation has transformed it into a transportation dead end, the bridge has lost much of its geopolitical potential. Today, it is a local project designed to resolve the urgent, but local problems of a small patch of land. Before unification with Russia, the peninsula was completely integrated with Ukraine, which covered its needs for foodstuffs, supplied it with 100% of coal and sugar, and 90% of fuel and 55% of oil products.1 The peninsula’s dependence on the Kerch ferry, the low capacity of which drops even further in bad weather, has become a focal point because of the limited supplies from Ukraine. Discontent among the Crimean people, or even social outbursts, cannot be excluded. The economic and financial blockade of Russia caused by the war with Ukraine has made the Kerch traffic interchange a challenge of huge dimensions. Russia has no choice: the problem must be solved either with the use of arms (occupation of the Ukrainian stretch of the Azov coast from Mariupol to Crimea), or by building a bridge across the Kerch Strait. If the first alternative fails, Russia will have to realize the latter in haste. It remains to be seen whether the game is worth the candle.